METODOLOGÍA EXPERIMENTAL PARA EL DESARROLLO DE COMPETENCIAS EN QUÍMICA INORGÁNICA CON ESTUDIANTES DE SEGUNDO SEMESTRE DE LA CARRERA DE PEDAGOGÍA EN QUÍMICA Y BIOLOGÍA, PERIODO OCTUBRE 2018 – ABRIL 2019 - Pilco Carrión, Roxana Alexandra (2019)
The present research was carried out at the National University of Chimborazo at Faculty of Sciences Education, Humanities and Technologies, in the career of Experimental Sciences in Chemistry and Biology Pedagogy, with the students of second semester in the Subject of Inorganic Chemistry I. The problem was the lack application of Experimental Methodology to development competencies in inorganic chemistry. The objective was to determine the importance of Experimental Methodology for development competencies in Inorganic Chemistry. The methodology used: analysis – synthesis was employed to collect information; the design of the research is non-experimental. The type of research was field and bibliographic which provided exact and accurate information, the level research is descriptive. The population with which we worked, were the second semester students of the Experimental career: Chemistry and Biology Pedagogy. As an instrument the survey was applied with the purpose of collect information and verify the existing problem in front of limitation to Experimental Methodology in development of competencies. After realizing analysis results it was identified that Experimental Methodology is important to development of competencies in Inorganic Chemistry, where the experimentation allows to get solutions about setting problems in the classroom. Although, set into students an independence, creativity and curiosity to learning and construct their own knowledge relating with development of competencies to a correct performance like Chemistry and Biology Pedagogies.